1997
DOI: 10.1007/s004210050199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different carbohydrate-electrolyte beverages on the appearance of ingested deuterium in body fluids during moderate exercise by humans in the heat

Abstract: To determine whether different forms of glucose (free and polymer) associated with sodium chloride influence the rate of water absorption during exercise in the heat, six men took part in five trials. Each trial included a passive heating session which resulted in a 2% loss of body mass, followed by 1h of treadmill exercise (at 50% of maximal oxygen uptake) in warm conditions (dry bulb temperature 35 degrees C, relative humidity 20%-30%). Immediately before exercise, the subjects were given either no fluid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Therefore, 2 H 2 O accumulation in plasma is more likely related to the gastric emptying rate of the ingested fluid (Costill 1990) than to the intestinal absorption rate of that fluid (Davis et al 1988;Gisolfi et al 1990). The present investigation was the first to evaluate the accumulation and time course of 2 H 2 O in both plasma and sweat during exercise-heat stress, at a time point less than 30 min (Koulmann et al 1997). …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, 2 H 2 O accumulation in plasma is more likely related to the gastric emptying rate of the ingested fluid (Costill 1990) than to the intestinal absorption rate of that fluid (Davis et al 1988;Gisolfi et al 1990). The present investigation was the first to evaluate the accumulation and time course of 2 H 2 O in both plasma and sweat during exercise-heat stress, at a time point less than 30 min (Koulmann et al 1997). …”
Section: Discussionmentioning
confidence: 95%
“…The former investigation (Armstrong et al 1987) appeared as a conference abstract, involved only four subjects (i.e., low statistical power) and utilized H 2 18 O as a stable isotope tracer. The latter investigation (Koulmann et al 1997) reported sweat deuterium oxide accumulation at a point 30 min after ingestion, but at no time points prior to 30 min. This hypothetical outcome, if confirmed, would provide novel support for the recommendations of sports medicine, military organizations (Casa et al 2000; Department of the Army and Air Force 2003) and physiologists (Sawka et al 2007) regarding the benefits of drinking before, or soon after exercise begins, in a warm or hot environment.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Only three studies (Armstrong, et al, 2010;Davis et al, 1985;Koulmann, et al, 1997) in the scientific literature have addressed this topic, and none were specifically designed to determine how rapidly ingested water starts to appear as sweat. For example, the seminal study by Armstrong et al (2010) determined fluid kinetics from ingestion to sweat secretion using deuterium oxide (D 2 O) enrichment during an hour of exercise in the heat.…”
Section: Introductionmentioning
confidence: 99%